2014
DOI: 10.4137/cin.s17641
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Subnetwork Detection Methods for Breast Cancer

Abstract: Subnetwork detection is often used with differential expression analysis to identify modules or pathways associated with a disease or condition. Many computational methods are available for subnetwork analysis. Here, we compare the results of eight methods: simulated annealing–based jActiveModules, greedy search–based jActiveModules, DEGAS, BioNet, NetBox, ClustEx, OptDis, and NetWalker. These methods represent distinctly different computational strategies and are among the most widely used. Each of these meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Significant pathways that are identified by different clustering methods often yield tens or hundreds of genes, making biological interpretation and validation challenging. Further, many clustering techniques such as Dynamic Tree Cut utilized in WGCNA rely on usersettable parameters, including minimum module size, and are sensitive to cluster splitting [8,9]. While many of these module detection methods perform optimally on some datasets, they may fail to effectively detect patterns in other datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Significant pathways that are identified by different clustering methods often yield tens or hundreds of genes, making biological interpretation and validation challenging. Further, many clustering techniques such as Dynamic Tree Cut utilized in WGCNA rely on usersettable parameters, including minimum module size, and are sensitive to cluster splitting [8,9]. While many of these module detection methods perform optimally on some datasets, they may fail to effectively detect patterns in other datasets.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, comparative studies on medically relevant data have reported poor consistency between individual methods ( Jiang and Gribskov, 2014 ) and questioned the merit of applying subnetwork-based methods altogether ( Staiger et al , 2013 )…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that model-based biomarker based on the activity of the JNK pathway robustly stratified neuroblastoma patients across different molecular backgrounds [ 3 ]. Computational models have already been used to provide an understanding of the dynamics of one or a few specific signaling pathways [ 16 18 ], however, the availability of comprehensive pathway-wide models [ 5 ] that transform decontextualized transcriptomics gene expression data into signaling activities, which in turn trigger cell functions that can be linked to cancer hallmarks, provide a quantitative framework to identify neuroblastoma functional drivers. Thus, we were not only able to reproduce the results of previous modeling studies that linked the inability of activating the JNK pathway to neuroblastoma bad prognostic but also to discover the pathways upstream responsible of its inhibition.…”
Section: Discussionmentioning
confidence: 99%